(untitled) (New Delhi, 2005)
Profiles all scientific management aspects of the horticultural crop genetic resources including their diversity, conservation and sustainable utilization. It also addresses vital concerns regarding management of horticultural crop genetic resources from diverse perspectives
Keywords: Plant genetic resources,Horticultural Crops,Di truyền học nông nghiệp,Di truyền học cây trồng; Plant genetic resources